KEARIFAN EKOLOGIS KAMPUNG MEGALITIK RINDI PRAIYAWANG, SUMBA TIMUR - I Made Geria (Balai Arkeologi Bali, 2014)
Rindi Praiyawang Site is the oldest traditional village in East Sumba which is rich in megalithic remains, such as stone tomb and menhir or penji. Characteristic of this megalithic site is the ancestor worship which still continues until today. This study aims to reveal the site of Rindi Praiyawang from the environmental aspect of view. The methods applied were library research, observation, and interview, while the analysis was done by inductive reasoning through descriptive explanation. This village space regulation has linear pattern which function sacred and profane. Stone tomb and menhirs are regarded as sacred megalithic remains for worshipping their ancestors. Until now, people of Rindi still maintain the tradition of ancestor worship, preserving nature and their environment in spite of modernization attack.Situs Rindi Praiyawang adalah sebuah perkampungan adat tertua di Sumba Timur yang kaya akan tinggalan megalitik, seperti kubur-kubur batu dan menhir atau penji. Ciri khas megalitik di situs ini, ialah pemujaan leluhur yang masih berlanjut hingga sekarang. Tulisan ini bertujuan untuk mengungkap Situs Rindi Praiyawang dari aspek pandang lingkungannya. Metode yang digunakan adalah studi kepustakaaan, observasi, dan wawancara, sedangkan tahap analisis dilakukan dengan penalaran induktif melalui upaya deskriptif-ekspalanatif. Tata ruang perkampungan ini memiliki pola linier yang berfungsi sakral dan profan. Kubur batu dan menhir merupakan tinggalan megalitik yang sangat disakralkan dalam upaya penghormatan terhadap leluhur. Sampai saat ini masyarakat rindi masih tetap mempertahankan tradisi pemujaan leluhur, menjaga alam dan lingkungannya meskipun di tengah serangan modernisasi.